2015
DOI: 10.2174/1874321801509010001
|View full text |Cite
|
Sign up to set email alerts
|

Continuous Versus Single-Injection Peripheral Nerve Blocks: A Prospective Cohort Study Comparing Procedural Time and Estimated Personnel Cost

Abstract: Background and Objectives: Continuous peripheral nerve blocks (CPNB) provide many additional benefits compared to single-injection peripheral nerve blocks (SPNB). However, the time and costs associated with CPNB provision have not been previously considered. The objective of this study was to compare the time required and estimated personnel costs associated with CPNB and SPNB. Methods: This IRB-exempt observational s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 19 publications
0
3
0
Order By: Relevance
“…When comparing PNB with a combination of standard and liposomal bupivacaine to PNB with standard bupivacaine alone, potential benefits are largely related to the avoidance of peripheral nerve catheter placement: enhanced patient comfort, reduced infection risk, ease of single-injection, and potential reduction in costs of care due to decreased resource utilization and time requirements for catheter placement and maintenance. 25 These same potential benefits would also be relevant compared with surgically placed perineural catheters, which have also been shown to reduce postoperative opioid consumption. 26 However, the long-term safety of liposomal bupivacaine in PNB has not been established.…”
Section: Discussionmentioning
confidence: 99%
“…When comparing PNB with a combination of standard and liposomal bupivacaine to PNB with standard bupivacaine alone, potential benefits are largely related to the avoidance of peripheral nerve catheter placement: enhanced patient comfort, reduced infection risk, ease of single-injection, and potential reduction in costs of care due to decreased resource utilization and time requirements for catheter placement and maintenance. 25 These same potential benefits would also be relevant compared with surgically placed perineural catheters, which have also been shown to reduce postoperative opioid consumption. 26 However, the long-term safety of liposomal bupivacaine in PNB has not been established.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 19 Additionally, a recent analysis showed that a single-shot peripheral nerve block takes a mean 505 seconds to complete when performed by an experienced regional anesthesia specialist. 2 This does not account for the additional time required for patient preparation, supply preparation, and additional delays in the setting of less experienced practitioners. Additionally, a cost analysis of peripheral nerve block and intra-articular injection revealed patient savings of 2.63% in those receiving intra-articular injection; a separate study showed a cost savings of $400.…”
Section: Discussionmentioning
confidence: 99%
“…Continuous perineural infusion can maintain analgesia for days but is met with challenges such as technical expertise, maintaining the catheter, and greater cost than a single injection. 4 One of the proposed solutions to extending the duration of long-acting local anesthetic is the addition of different classes of analgesics with the local anesthetic. Clonidine is one example that has been shown to prolong the duration of analgesia.…”
mentioning
confidence: 99%